Maternal near-miss in N'Djamena Mother and Child Hospital, Chad - Gabkika Bray Madoue; Saleh Abdelsalam; Doumbia Madjouma Badara Aliou; Adoum Offi; Sabre Emile; Ehdjolbo Pallai; Askemdet Obelix (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2017)
Background: Maternal near-miss describes a woman who almost died but survived a complication that occurred during pregnancy, childbirth or within the 42 days following pregnancy termination. The prevalence of maternal near-miss is variable around the world. In Chad no previous survey has been performed on maternal near-miss. Objective: To describe the characteristics of patients affected by maternal near-miss in N'Djamena mother and child hospital. Results: During the 6-month period (January 1st to June 30th 2016) of data collection there were 4,857 live births. The 100 most severe cases of near-miss (2.06 % of all deliveries) were selected. The majority of these patients (96%) were ≤ 35 years old. Seventy six per cent had had 0-3 prenatal consultations. A high proportion of women had been referred (84%). Main morbidities were: haemorrhage (62%) and hypertensive complication (24%) followed by abortion (6%). Conclusion: Maternal near-miss is often recorded in our hospital. Haemorrhage and hypertension are the main pathologies registered.